Preparation method for forming micro-nano hydrophobic coating by dip-coating fabric surface

By forming a micro-nano hydrophobic coating on the surface of natural fiber fabrics, the environmental pollution problem during the treatment of existing waterproof materials is solved, and the hydrophobic properties of natural fiber materials are improved, achieving environmental protection, degradation and efficient hydrophobic effects.

CN119800707APending Publication Date: 2025-04-11JILIN INST OF CHEM TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510044683.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing waterproof materials will produce harmful substances during incineration or landfill treatment, resulting in environmental pollution and health hazards. The hydrophobic properties of natural fiber textile materials are insufficient, which limits their application.

Method used

By dipping the surface of natural fiber fabrics, a roughness coating is constructed by dipping the surface of natural fiber fabrics, a roughness coating is constructed using hydrophobic solvents and micro-nano solid particles to increase the hydrophobic angle and form three hydrophobic layers.

Benefits of technology

It realizes the efficient hydrophobic properties of natural fiber fabrics. The product still maintains good hydrophobic effects after water soaking, and has environmentally friendly degradation properties during environmental treatment, avoiding the spread of pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238031060000061
    Figure BDA0005238031060000061
  • Figure BDA0005238031060000062
    Figure BDA0005238031060000062
  • Figure BDA0005238031060000071
    Figure BDA0005238031060000071
Patent Text Reader

Abstract

The invention discloses a preparation method for forming a micro-nano hydrophobic coating by dip-coating on the surface of a fabric, and relates to the technical field of hydrophobic modification of natural fiber fabrics. According to the first part of the product, the selected fabric is formed by weaving natural materials through pulping, spinning and other processes, the fabric hydrophobic coating is composed of two parts, the first part is that a hydrophobic solution and the fabric are selected to construct a microcosmic basic structure, the second part is that a hydrophobic layer is secondarily covered with a mixed solvent, and micro-nano solid particles are added; by utilizing the properties of a silane coupling agent and polydimethylsiloxane, the silane coupling agent and the polydimethylsiloxane are mixed according to a proportion, and the mixture is smeared on the surface of the fabric to construct a rough coating. The preparation method has the advantages that the hydrophobicity is good, and a modified product can still have a good hydrophobic effect after being soaked in water for a long time; the environment is protected, when landfill treatment is needed, the product can be degraded in the natural environment for two years, and when combustion treatment is needed, only carbon dioxide, water and other environment-friendly gases can be generated; water and soil loss is prevented, the hydrophobic effect can be kept in the soil for two years, and afforestation and desert greening are facilitated; the soil is fertile, and the product is rich in sodium ions after being soaked in sodium methyl silicate, so that the nutrient of the soil is increased, and the soil is kept in a fertile state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of super-hydrophobic modification of natural fiber fabrics. Background technology:

[0002] Since the 1950s, materials such as polyvinyl chloride (PVC) and polypropylene (PP) have been widely used in various fields, and their global production has increased year by year. Because of their good stability, heat resistance and flexibility, they are easy to carry and have a wide range of applications, and have become indispensable materials in modern life. They are widely used in the waterproof cloth industry and have obvious effects. Since polyvinyl chloride (PVC) and polypropylene (PP) are non-degradable, they are mostly disposed of by landfill, incineration and other methods after being discarded. However, these products often contain extremely harmful bacteria. If they spread, they will cause pollution and harm society. After this high-temperature incineration process, other toxic substances such as dioxins, nitrogen and sulfur oxides will be produced. Therefore, new environmentally friendly and degradable waterproof materials are an important trend in the development of social health and environmental protection. Natural fibers come from organic raw materials. According to their original sources, natural fibers can be divided into plant fibers (mainly composed of cellulose) and animal raw material fibers (mainly composed of protein). The natural fibers existing in nature mainly include straw, cotton, hemp, silk and animal hair. The molecular components of cotton and hemp are mainly cellulose, while the molecular components of silk and hair are mainly protein. Natural fibers have the advantages of biodegradability, good biocompatibility, renewability, environmental friendliness and non-toxicity, and have received more and more attention in various functional material fields. Due to the rich hydroxyl groups in the cellulose structure, cellulose has excellent hydrophilicity, which has greatly limited the application of cellulose in the field of hydrophobic materials. To achieve the wide application of natural fiber textile materials, it is particularly important to improve its hydrophobic properties. At present, there are two main ways to modify cellulose to make it hydrophobic: one is to modify natural fibers with low surface energy substances, including siloxanes, fluoroalkyl silanes, stearic acid and some synthetic polymers; the other method is to construct a hydrophobic surface with micro / nano rough structures. According to the two approaches, this paper reviews the modification of natural fiber textile materials with hydrophobic solutions, the construction of hydrophobic surface modification with micro / nano rough structures, and the use of adhesives to fix microstructure modification, so that the materials can obtain excellent hydrophobic properties. Therefore, it is necessary to design a new type of environmentally friendly and degradable waterproof material to achieve social health and environmental protection development in order to solve the above technical problems. Summary of the invention:

[0003] In view of the shortcomings of the above-mentioned technologies, the purpose of the present invention is to provide a new type of environmentally friendly degradable waterproof material to solve the problem of pollution spread and environmental damage caused by material incineration and landfill in the prior art.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A preparation method for forming a micro-nano hydrophobic coating by dipping on a fabric surface, wherein the first part is a selected fabric (1) made of natural materials, such as cotton, straw, wood and the like, and woven through pulping, spinning and other processes; the second part is the micro-nano super hydrophobic coating, the micro-nano super hydrophobic coating is composed of two solvents, the first solvent (2) is a selected hydrophobic solvent, the first solvent (2) and the fabric (1) are dehydrated and cross-linked through a chemical reaction to construct a fabric (3) with a microstructure; the second solvent (4) is added with selected micro-nano solid particles under the condition of a specific solvent (silane coupling agent, polydimethylsiloxane), and is smeared on the surface of the fabric (3) in a proportion to construct a roughness coating (5) to increase the hydrophobic angle, and the selected micro-nano solid particles are micro-nano solid particles of 50 nm silicon dioxide particles.

[0006] The working principle of this technical solution is:

[0007] like Figure 1 As shown, when the inner angle (hydrophobic angle) θ between the water droplet and the contact surface is less than 90°, the contact surface is a hydrophilic surface, when the inner angle (hydrophobic angle) θ between the water droplet and the contact surface is greater than 90°, the contact surface is a hydrophobic surface, and when the inner angle (hydrophobic angle) θ between the water droplet and the contact surface is greater than 150°, the contact surface is a micro-superhydrophobic surface; when the surface roughness of the material is very high, the droplet is in a metastable state on the solid surface. At this time, the Wenzel model is no longer applicable. Therefore, Cassie and Baxter further proposed the Cassie-Baxter model, which assumes that a large amount of air is trapped between the solid / liquid interface and that the water droplet has no penetration on the rough structure surface. In this case, the contact angle can be expressed by the Cassie-Baxter equation; in actual situations, the wetting state is between the Wenzel and Cassie models, which is manifested as water partially wetting the rough surface of the material, so it is expressed by the Wenzel-Cassie equation.

[0008] like Figure 2 As shown, this product is composed of three hydrophobic layers, namely sodium silicate, silicon dioxide and polydimethylsiloxane. The modified fabric has excellent hydrophobic effect, is wear-resistant and foam-resistant, can be used in various scenes in life, and has good environmental protection and health effects.

[0009] A preparation method for forming a micro-nano hydrophobic coating by dipping on a fabric surface, wherein the fabric (1) is fully immersed in the hydrophobic solvent (2), the hydrophobic solvent (2) is diluted to 5% with distilled water, the ratio of the original solution to the distilled water is 1:20, the hydrophobic solvent is selected as organic sodium silicate, and is fully stirred evenly, and the soaking is required to be at normal pressure (0.1013Mpa) and the temperature is raised to 60°C. Information can be obtained from Table (1) that the hydrophobic angle is optimal when the organic sodium silicate concentration reaches 6%, and information can be obtained from Table 3 that the hydrophobic angle is optimal when the temperature is 60°C. The angle is optimal, the fabric (1) is immersed in the hydrophobic solvent (2) for 2 hours, taken out, and naturally dried in an environment with a temperature of 25°, and a micro-basic structure fabric (3) is constructed through chemical reaction dehydration and cross-linking. The micro-basic structure fabric (3) is that the fabric (1) contains a large number of hydroxyl functional groups (-OH) and the hydroxyl functional groups (-OH) in the hydrophobic solvent (2), and the two are dehydrated and cross-linked to form a microstructure (Si-O-Si), thereby reducing the number of hydroxyl functional groups (-OH) in the hydrophilic group of the fabric (1).

[0010] Further defined, a preparation method for forming a micro-nano hydrophobic coating by dipping on the surface of a fabric, designing an experiment on the relationship between the proportion of organic sodium silicate and the hydrophobic angle, and obtaining the data in Table 1, respectively preparing 1%, 3%, 6%, 15%, and 20% organic sodium silicate solvent, and using a contact angle measuring instrument to measure the hydrophobic angle, the hydrophobic angles are 109.35°, 120.29°, 121.82°, 116.57°, and 97.64°, respectively. Figure 6 As shown in the figure, when the proportion of sodium organosilicate is 6%, the maximum hydrophobic angle is measured, and the proportion of sodium organosilicate is 6% which is the most suitable. The experiment on the relationship between the immersion time of fabric (1) in sodium organosilicate and the hydrophobic angle is designed. The data in Table 2 are obtained. The immersion time is adjusted to 0.5h, 2h, 6h, and 12h respectively. After testing, the hydrophobic angles are 111.85°, 125.28°, 126.74°, and 129.97° respectively. Figure 7 As shown, the fabric (1) is immersed in the sodium organosilicate for 2 hours, which takes less time and the best hydrophobic angle is measured. The most suitable time for the fabric (1) to be immersed in the sodium organosilicate is 2 hours. An experiment on the relationship between the immersion temperature and the hydrophobic angle of the fabric (1) in the sodium organosilicate is designed. According to the data in Table 3, the immersion temperatures are adjusted to 20°C, 40°C, 60°C, and 90°C of the sodium organosilicate solvent, and after testing, the hydrophobic angles are 109.41°, 116.95°, 126.27°, and 128.37°, respectively. Figure 8 As shown, when the fabric (1) is immersed in sodium organosilicate at a temperature of 60°C, the preparation cost is low and the measured hydrophobic angle is optimal. The data show that the fabric (1) is most suitable when immersed in sodium organosilicate at a temperature of 60°C.

[0011] Further defined, a preparation method of forming a micro-nano hydrophobic coating by dipping on a fabric surface, such as Figure 3 , 4 As shown in the figure, the surface area of ​​the fabric increases after being soaked in a hydrophobic solvent, and the pore size on the surface of the fabric becomes smaller, making it difficult for water to penetrate.

[0012] A preparation method for forming a micro-nano hydrophobic coating by dipping on the surface of a fabric, the solvent (4) is prepared, 50nm micro-nano solid particles of silica particles are added to a mixed solution of 75% alcohol substances and stirred to fully disperse them, to obtain a product (A), which is placed in a flask for use.

[0013] Further defined, a preparation method for forming a micro-nano hydrophobic coating by dipping on the surface of a fabric, designing a solid particle 50nm silica particle mass and a silane coupling agent mass to affect the hydrophobic angle experiment, and obtaining the data in Table 4, when preparing 20ml of solvent, the mass of the silane coupling agent is fixed, and the mass of the 50nm silica is changed to 0.5g, 1g, 2g, and 3g respectively. When the mass of the silane coupling agent is 1g, the hydrophobic angle is measured by a contact angle measuring instrument, and is obtained by Fig. 9 As shown, the hydrophobic angles are 139.54°, 143.85°, 147.37°, and 147.21° respectively; when the mass of the silane coupling agent is 5g, the hydrophobic angles are 124.75°, 134.26°, 135.42°, and 135.81° respectively. The data show that when the mass of the silane coupling agent is 1g and 5g, the mass of the solid particles 50nm silica particles is 2g, which is the most suitable.

[0014] Further defined, a preparation method for a micro-nano hydrophobic coating formed by dip coating on the surface of a fabric, measuring a silane coupling agent (the concentration is required to be 75% of the mass percentage of silica), fully mixing it into the above-mentioned product (A) mixed solution to obtain a product (B) and a by-product (C), transferring the magnetic stirrer to atmospheric pressure (0.1013Mpa), stirring at 30°C for 1h, and then stopping stirring, the product (B) is a silane coupling agent and 75% of an alcohol substance dehydrated and cross-linked, the methoxy group (-CH3O) in the silane coupling agent is removed to form a hydroxyl group (-OH), and the hydroxyl group (-OH) on the outer surface of the micro-nano solid particle 50nm silica particle is dehydrated and cross-linked again to form a microstructure (Si-O-Si), and the by-product (C) is removed by a distillation device, and the by-product (C) is a mixed solution of a small amount of methanol and ethanol, which is placed aside.

[0015] Further defined, a preparation method for forming a micro-nano hydrophobic coating by dipping on the surface of a fabric, measuring polydimethylsiloxane (the concentration is required to be 50% of the mass of the silane coupling agent), fully mixing it into the product (B), stirring it for 1 hour at 25°C under normal pressure (0.1013Mpa), and then taking it out to obtain a solvent (4), wherein the solvent (4) is (-H) in the polydimethylsiloxane and a small amount of hydroxyl (-OH) remaining in the product (B) are dehydrated and cross-linked again, effectively reducing the number of hydrophilic groups and increasing the viscosity of the solvent, having a better hydrophobic effect, and increasing the surface roughness of the fabric (3), and the solvent (4) is evenly applied to the fabric (3) to construct the roughness coating (5), and it is required to dry naturally at a temperature of 60°C to effectively establish a "lotus effect" structure.

[0016] Further defined, a preparation method for forming a micro-nano hydrophobic coating by immersion coating on the surface of a fabric, as shown in Figure (5), after being treated with a solvent (4), a large number of solid particles are attached to the surface of the fiber, and the fabric soaked in a hydrophobic solvent has an increased surface area that can accommodate more solid particles, the pore size of the fabric surface continues to shrink, and the hydrophobic effect is enhanced.

[0017] Table 1 Relationship between fabric soaked in different concentrations of organosilicon acid and hydrophobic angle

[0018]

[0019] Table 2 Relationship between the hydrophobic angle and the time of fabric soaking in hydrophobic solvent

[0020]

[0021] Table 3 Relationship between different temperatures and hydrophobic angles of fabrics immersed in hydrophobic solvents

[0022]

[0023] Table 4 Relationship between the mass of silica and silane coupling agent and the hydrophobic angle in the preparation of 20 ml solvent

[0024] Description of the drawings:

[0025] Figure 1 : Cassie-Baxter model and Wenzel-Cassie model

[0026] Figure 2 :Product production principle

[0027] Figure 3 : Scanning electron microscope image of untreated fabric

[0028] Figure 4: Scanning electron microscope image of fabric treated with 6% sodium organosilicate

[0029] Figure 5 :Scanning electron microscope image of fabric treated with 6% sodium organosilicate and solvent

[0030] Figure 6 : Hydrophobic angle of fabric after 6% sodium organosilicate treatment

[0031] Figure 7 : Hydrophobic angle of fabric after soaking in 6% sodium organosilicate for 2 hours

[0032] Figure 8 : Fabric hydrophobicity after soaking in 6% sodium silicate at 60℃ for 2h

[0033] Fig. 9 : Hydrophobic angle of fabric after treatment with 6% sodium organosilicate and solvent Specific implementation method:

[0034] Example 1: The fabric with a size of 0.1m×0.1m was fully soaked in 1%, 3%, 6%, 15%, and 20% sodium methyl silicate solutions respectively, and soaked for 12 hours at a temperature of 40°C. The soaked fabric was taken out and placed in a ventilated place to dry naturally. The contact angle measuring instrument was used to measure the hydrophobic angles of 109.35°, 120.29°, 121.82°, 116.57°, and 97.64° respectively. It was concluded that the hydrophobic effects of the samples after soaking and drying at different concentrations were different, and the most suitable ratio of sodium methyl silicate was 6%.

[0035] Example 2: A fabric of size 0.1m×0.1m was fully soaked in 1%, 3%, 6%, 15%, and 20% potassium methyl silicate solution respectively, and soaked for 12 hours at a temperature of 40℃. The soaked fabric was taken out and placed in a ventilated place to dry naturally. The hydrophobic angle was measured by a contact angle measuring instrument, which was close to the corresponding concentration of sodium methyl silicate solution. It was concluded that the hydrophobic effect of samples after soaking and drying at different concentrations was different, and the most suitable ratio was 6% potassium methyl silicate.

[0036] Embodiment 3: The fabric with the size of 0.1m×0.1m was fully immersed in 6% sodium methyl silicate solution at 40°C for 0.5h, 2h, 6h and 12h respectively. The fabric after immersion was taken out and placed in a ventilated place to dry naturally. The hydrophobic angle was measured by a contact angle measuring instrument. The measured hydrophobic angles were 111.85°, 125.28°, 126.74° and 129.97° respectively. It was concluded that the hydrophobic effect of the samples after drying for different immersion times was different, and the most suitable immersion time for the fabric in sodium organosilicate was 2h.

[0037] Embodiment 4: A fabric with a size of 0.1m×0.1m is fully immersed in a 6% sodium methyl silicate solution. Under the condition of a soaking time of 2h, the soaking temperature is adjusted to 20℃, 40℃, 60℃, and 90℃ respectively. After soaking, the fabric is taken out and placed in a ventilated place to dry naturally. The hydrophobic angle is measured by a contact angle measuring instrument, and the measured hydrophobic angles are 109.41°, 116.95°, 126.27°, and 128.37°, respectively. It is concluded that the hydrophobic effects of the samples after drying at different soaking temperatures are different, and it is most suitable for the fabric to be soaked in sodium organosilicate at 60℃ for 2h.

[0038] Example 5: When preparing 20 ml of solvent, different amounts of micro-nano solid particles 50 nm silica particles are added to a mixed solution of 75% alcohol substances and stirred to make them fully dispersed. The masses are 0.5 g, 1 g, 2 g, and 3 g respectively, and placed in a flask for standby use; 1 g of silane coupling agent is measured and fully mixed into the above flask to obtain products and by-products. The magnetic stirrer is transferred to atmospheric pressure (0.1013 MPa), and after stirring at 30°C for 1 hour, the stirring is stopped, and the distillation device is modified to evaporate the low-boiling point solvent by-product at atmospheric pressure. The by-product is an alcohol substance that can be recycled and reused. Measure 0.5g of polydimethylsiloxane, mix them fully into the product, stir them for 1h at 25℃ under normal pressure (0.1013Mpa), and take them out to obtain a mixed solvent. Apply the solvents evenly on the surfaces of the above-mentioned fabrics as a hydrophobic layer for secondary coverage. Apply about 20ml of solvent to the fabric of 0.1m×0.1m, and dry them naturally at 60℃. Use a contact angle measuring instrument to measure the hydrophobic angles, which are 139.54°, 143.85°, 147.37°, and 147.21° respectively; change the mass of the silane coupling agent to 5g, and after the above process, the hydrophobic angles are 124.75°, 134.26°, 135.42°, and 135.81° respectively. It is concluded that the mass of the silane coupling agent is 1g and the mass of the micro-nano solid particles 50nm silica particles is 2g, which is the most suitable.

[0039] On the basis of the above scheme:

[0040] Compared with the existing technology, the advantages of the present invention are: Compared with the waterproof cloth made of polyvinyl chloride (PVC), polypropylene (PP) and other materials at present: 1. Good hydrophobicity, the modified product can be soaked in water for a long time and still have a good hydrophobic effect. 2. Environmental protection, when the above product needs to be landfilled, it can be degraded in two years in the natural environment without causing harm to the soil. When it needs to be burned, it will only produce carbon dioxide, water and other environmentally friendly gases.

[0041] Compared with the existing technology, the advantages of the present invention are: it can be applied to the inner layer of soil and deserts: 1. Preventing soil erosion. After testing, the above product can maintain a hydrophobic effect in the soil for up to two years, avoiding water loss below the soil, keeping the soil moist, and being conducive to afforestation and desert greening; 2. Fertile soil. After being soaked in sodium methyl silicate, the above product is rich in sodium ions, which is conducive to increasing soil nutrients and keeping the soil fertile.

[0042] Compared with the existing technology, the advantages of the present invention are: strong plasticity, can adapt to various shapes and still maintain a hydrophobic state, can be used to make waterproof clothing, has strong resistance and good effect, and can still maintain a hydrophobic state after being soaked in water for a long time.

Claims

1. A preparation method for forming a micro-nano hydrophobic coating by dipping on a fabric surface, characterized in that: The first part is a selected fabric (1) made of materials such as cotton, straw, and wood through pulping, spinning, and other processes. The second part is the micro-nano super hydrophobic coating, which is composed of two parts. The first part is a selected hydrophobic solvent (2), and the hydrophobic solvent is selected from organic silicates, such as sodium methyl silicate and potassium methyl silicate. The hydrophobic solvent (2) and the fabric (1) undergo chemical reaction, dehydration, and cross-linking to construct a fabric (3) with a microstructure. The second part contains a solvent (4) containing micro-nano particles, which is applied to the surface of the fabric (3). The secondary coverage increases the surface roughness and increases the hydrophobicity of the fabric (3).

2. According to claim 1, a preparation method for forming a micro-nano hydrophobic coating by dipping on a fabric surface, characterized in that: The fabric (1) is fully immersed in the solvent (2) of a certain concentration and stirred evenly. During the immersion, the temperature is 60° to 90° C. under normal pressure for 2 to 4 hours. After the immersion, the fabric is naturally dried in an environment at a temperature of 25°. The fabric (3) is dehydrated and cross-linked through chemical reaction to construct a microscopic basic structure. The microstructure of the fabric (3) is a microstructure (Si-O-Si) constructed by dehydration and cross-linking between the hydroxyl functional groups (-OH) in the fabric (1) and the hydroxyl functional groups (-OH) in the hydrophobic solvent (2), which greatly reduces the hydrophilicity of the fabric (1).

3. According to claim 1, a preparation method for forming a micro-nano hydrophobic coating by dipping on a fabric surface, characterized in that: The preparation method of solvent (4) is as follows: 50 nm silicon dioxide is added to 50% to 75% alcohol substance, stirred to fully disperse it, and obtain product (A). On this basis, a certain amount of silane coupling agent is added, and the reaction is stirred for 1 hour at normal pressure and a reaction temperature of 30° C. to obtain product (B) and by-product (C). The distillation device is modified to distill out the low-boiling point solvent by-product (C) at normal pressure. The by-product (C) is an alcohol substance, which can be recycled and reused and is applied to the preparation method of solvent (4).

4. According to claim 1, a preparation method for forming a micro-nano hydrophobic coating by dipping on a fabric surface, characterized in that: Polydimethylsiloxane (the concentration required is 50% of the mass of the silane coupling agent) is measured and fully mixed into the product (B). After stirring at a temperature of 25° C. for 1 hour, the mixture is taken out to obtain a solvent (4). The solvent (4) is the (-H) in the polydimethylsiloxane and a small amount of hydroxyl (-OH) remaining in the product (C) which are dehydrated and cross-linked again to effectively reduce the number of hydrophilic groups and increase the viscosity of the solvent, thereby having a better hydrophobic effect. The solvent (4) is evenly applied to the fabric (3) to increase the surface roughness of the fabric (3) and construct a coating (5). The coating is required to be naturally dried in an environment with a temperature of 60° to construct a "lotus effect" structure.

5. According to claim 1, a preparation method for forming a micro-nano hydrophobic coating by dipping on a fabric surface, characterized in that The fabric (5) passes the hydrophobic angle test, and the inner angle (hydrophobic angle) θ between the water droplet and the surface of the fabric (5) is greater than 90°, indicating that the fabric (5) is a fabric with hydrophobic function.

Citation Information

Cited By

  • Production process of fluoride-free dynamic waterproof suede shoe leather

    CN121087805A

  • Production process of fluorine-free dynamic waterproof suede leather

    CN121087805B